PENGARUH KEKUATAN DRAWING, STABILITAS LENGAN PENUMPU DAN KECEPATAN LAJU ANAK PANAH TERHADAP AKURASI TEMBAKAN DIVISI COMPOUND JARAK 50 METER - Yudho, Fitriadi Sandhi Nugroho; Sulaiman, Iman; Lubis, Johansyah; Sujarwo, Sujarwo (Jurnal Porkes, 2025)
The accuracy of compound archery shots is influenced by various complex technical factors. This study aims to analyze the direct and indirect effects of drawing strength, horizontal and vertical arm stability, and arrow velocity on shooting accuracy at a distance of 50 meters. The method used is quantitative with an associative causal design through path analysis. The research subjects consisted of 27 compound archery athletes from DKI Jakarta. Data were collected through measurements of drawing strength, arm stability, arrow speed, and shooting accuracy, then analyzed using the Generalized Linear Model (GLM). The results showed that the three technical variables had a significant direct effect on accuracy: drawing strength (β = 0.396; p = 0.025), horizontal stability (β = 0.356; p = 0.042), and vertical stability (β = 0.349; p = 0.045). Arrow speed was also found to be a significant mediator for the indirect effect of the three independent variables on accuracy. The conclusion of this study is that shooting accuracy is complexly influenced by a combination of drawing strength, arm stability, and arrow speed.